Investigating the interplay of Chinese EFL teachers' proactive personality, flow, and work engagement - Dai, Kun; Wang, Yongliang (Journal of multilingual and multicultural development, 2025)
Recently, researchers have focused on various factors influencing work engagement, particularly in the EFL context. In this vein, this study was carried out to investigate the relationship among proactive personality, flow, and work engagement in China. In so doing, three instruments including Proactive Personality Scale, Work-Related Flow Inventory (WOLF), and Work and Well-Being Survey (UWES) were used. Employing a convenience sampling method, 350 English teachers were selected from 20 provinces in China. Structural equation modeling (SEM) was utilized to analyze the obtained data. The findings demonstrated a positive correlation among EFL teachers' flow, proactive personality, and work engagement. The results of SEM also indicated that work engagement could be predicted by both flow and proactive personality; however, flow had more predictive power. The findings from this study have both theoretical and practical implications for second/foreign language researchers and different stakeholders.